PENGGUNAAN MODEL PEMBELAJARAN MULTILEVEL GROUP UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MATERI KPK DAN FPB DI KELAS VI SDN KETAWANG KARAY I KEC. GANDING KAB. SUMENEP SEMESTER 1 TAHUN PELAJARAN 2018/2019 - Rahwini Rahwini (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This study aims to improve the activities and mathematics learning outcomes of the KPK and FPB material in class VI students of Ketawang Karay I Elementary School in Ganding Subdistrict, Sumenep Regency, 1st Semester Academic Year 2018/2019 using the Multilevel Group learning model. This type of research is classroom action research in collaboration with colleagues. The results of the study showed that the use of the Multilevel Group learning model could increase the activeness of students in the Mathematics learning material of the KPK and FPB. In the aspect of confidence, in the first cycle with good categories, 54% confidence aspects, 69% activeness aspects, 46% learning motivation aspects, and 62% collaboration aspects. In the second cycle with a good category, it increased the self-confidence aspect to 92%, the activeness aspect to 85%, the learning motivation aspect to 85%, and the collaboration aspect to 77%. The results also show that the use of the Multilevel Group learning model can improve student learning outcomes in the Mathematics learning material of the KPK and FPB. In the pre-cycle stage the average grade of 55 with classical completeness was 23%, in the first cycle the average grade was 71 with 62% classical completeness, and in the second cycle the average value increased to 84 with 92% classical completeness.